Synthesis and Antitumor Activity of Erlotinib Derivatives Linked With 1,2,3-Triazole - Deng, Peng; Sun, Ge; Zhao, Jie; Yao, Kaitai; Yuan, Miaomiao; Peng, Lizeng; Mao, Longfei (Frontiers in Pharmacology, 2022)
Cervical cancer is one of the most important cause of cancer-related death and presents a major public health problem in many countries. To search for more novel anti-tumor agents against cervical cancer, fourteen erlotinib-linked 1,2,3-triazole compounds were designed, synthesized and evaluated for their anti-tumor activity. The compounds were confirmed by 1H NMR, 13C NMR and HR MS. Antitumor activity assay results indicated that six of those compounds have remarkable inhibitory activity against human cervical cancer Hela cells in vitro, among which compound 4m was the most potent with IC50 of 3.79 M, and compounds 4k, 4i, 4l, 4d and 4n also demonstrated remarkable antitumor activity with IC50 of 3.79 M, 4.16 M, 4.36 M, 7.02 M and 8.21 M. We found three of the most potent compounds 4d, 4k and 4l induced potent apoptosis and cell cycle arrest in Hela cells, and compounds 4d and 4l significantly restrained the cell colony formation and showed moderate EGFR inhibitory activity with IC50 of 13.01 M and 1.76 M. Therefore, these experiments indicate that these erlotinib-linked 1,2,3-triazole compounds are potential to act as effective anti-cancer agents against cervical cancer.